Blockade of extracellular NM23 or its endothelial target slows breast cancer growth and metastasis - Yokdang, Nucharee (Integr Cancer Sci Ther, 2015)
BACKGROUND: Nucleoside Diphosphate Kinase (NDPK), described as NM23 a metastasis suppressor, is found in the culture medium of cancer cells lines suggesting that the kinase may have an extracellular role. We propose that extracellular NM23 released from breast cancers in vivo stimulates tumor cell migration, proliferation and endothelial cell angiogenesis in support of metastasis development. METHODS: NM23 in the bloodstream of immunocompromised mice carrying human triple-negative breast cancers or in breast cancer patients was measured by ELISA. Primary and metastatic tumor development, the impact of blockade of NM23 and/or its stimulation of nucleotide receptors were measured using in vivo imaging. NM23 expression data in the Curtis breast dataset was examined to test our hypothesis that NM23 may play a mechanistic role in breast cancer development. RESULTS: SCID mice carrying metastatic MDA-MB-231Luc+ triple-negative human breast tumor cells elaborate NM23 into the circulation correlated with primary tumor growth. Treatment of mice with the NM23 inhibitor ellagic acid (EA) or the purinergic receptor antagonist MRS2179 slowed primary tumor growth. At 16 weeks following implantation, lung metastases were reduced in mice treated with EA, MRS2179 or the combination. Expression of NM23 in the Curtis breast dataset confirmed a likely role for NM23 in tumor metastasis. CONCLUSIONS: Extracellular NM23 may constitute both a biomarker and a therapeutic target in the management of breast cancer.